Preserving and Exploring Transition of Indigenous Knowledge on Traditional Healing Ritual Among Melanau Community in Mukah Division of Sarawak - Muhammad Faiz, Arshad (UNIMAS PUBLISHER, 2025)
Traditional healing rituals are a part of Indigenous Knowledge that has been utilized by indigenous communities as a healthcare system because it is significant and more profoundly established and complex than is generally perceived. In today’s modern world, Indigenous Knowledge is experiencing extinction due to the fact that it has been ignored and not documented. This research focused on preserving and exploring transition of Indigenous Knowledge on traditional healing rituals among the Melanau community in Mukah Division (Mukah, Dalat and Oya) of Sarawak. There are three main objectives of this research; (1) to identify the importance of preserving Indigenous Knowledge on traditional healing rituals; (2) to analyze the transition of Indigenous Knowledge on traditional healing ritual among the Melanau community and; (3) to examine the function of sago (balau) and the changes in its importance in Melanau community and traditional healing ritual. This qualitative research involved 20 informants who consisted of a Melanau traditional healer, a community leader, cultural related authorities and three groups from the Melanau community which are the elderly, adult, and youth group from Mukah Division. The informants were selected through a purposive sampling method and the data was collected through in-depth interviews. The findings of this study revealed that there was only one Melanau traditional healing ritual that is still practiced which is the dakan/bilum healing rituals and there are only two Melanau traditional healers available. This study also discovered that dance, museum, and oral narrations are some of the ways used to preserve this Indigenous Knowledge. Modern medicine, religious conversion and restrictions are the main factors that impacted the Melanau traditional healing rituals. This research also discovered that balau or sago is connected to the Melanau way of life because it is the main source of food, income, traditional healing rituals and many other usages. This research is significant because it iv contributed to the corpus of knowledge on preservation of the Indigenous Knowledge on Melanau traditional healing ritual among Melanau community. The policy implication is the need to establish protective, inclusive, and empowering frameworks that safeguard Indigenous Knowledge, promote cultural preservation, and integrate traditional wisdom into sustainable development and modern systems while respecting indigenous rights and self- determination. Governments, NGOs, and academic institutions must work collaboratively with indigenous communities to ensure IK remains vibrant and impactful for future generations.